Runner - Deuker, Carl, 1950- (Houghton Mifflin, 2005)
Living with his alcoholic father on a broken-down sailboat on Puget Sound has been hard on seventeen-year-old Chance Taylor, but when his love of running leads to a high-paying job, he quickly learns that the money is not worth the risk.